2015
DOI: 10.1634/theoncologist.2014-0493
|View full text |Cite
|
Sign up to set email alerts
|

Delays in Breast Cancer Presentation and Diagnosis at Two Rural Cancer Referral Centers in Rwanda

Abstract: Background. Breast cancer incidence is increasing in low-and middle-income countries (LMICs). Mortality/incidence ratios in LMICs are higher than in high-income countries, likely at least in part because of delayed diagnoses leading to advanced-stage presentations. In the present study, we investigated the magnitude, impact of, and risk factors for, patient and system delays in breast cancer diagnosis in Rwanda. Materials and Methods. We interviewed patients with breast complaints at two rural Rwandan hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

26
255
9
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 188 publications
(296 citation statements)
references
References 32 publications
26
255
9
6
Order By: Relevance
“…A growing number of small studies have examined the diagnostic and treatment delays and barriers to care experienced by breastcancer patients in LMICs, including in sub-Saharan Africa [16][17][18][19][20][21]; these demonstrate that patients experience long delays between initial symptoms and presentation at a health facility (patient delay) and then between first presentation and definitive diagnosis or treatment (provider delay). At two facilities in Rwanda, delay between initial development of symptoms and ultimate receipt of a diagnosis was 15 months; patient and provider delays were equally long, and both appeared to contribute to late-stage disease [21]. Reasons for patient delays cited in studies from sub-Saharan Africa include patients' lack of awareness of breast cancer symptoms and their seriousness [20][21][22][23], fear of a cancer diagnosis [21,23], use of traditional healers [21][22][23], and financial concerns about treatment [20,21].…”
Section: Breast Cancer Mortality In Lmicsmentioning
confidence: 99%
See 2 more Smart Citations
“…A growing number of small studies have examined the diagnostic and treatment delays and barriers to care experienced by breastcancer patients in LMICs, including in sub-Saharan Africa [16][17][18][19][20][21]; these demonstrate that patients experience long delays between initial symptoms and presentation at a health facility (patient delay) and then between first presentation and definitive diagnosis or treatment (provider delay). At two facilities in Rwanda, delay between initial development of symptoms and ultimate receipt of a diagnosis was 15 months; patient and provider delays were equally long, and both appeared to contribute to late-stage disease [21]. Reasons for patient delays cited in studies from sub-Saharan Africa include patients' lack of awareness of breast cancer symptoms and their seriousness [20][21][22][23], fear of a cancer diagnosis [21,23], use of traditional healers [21][22][23], and financial concerns about treatment [20,21].…”
Section: Breast Cancer Mortality In Lmicsmentioning
confidence: 99%
“…At two facilities in Rwanda, delay between initial development of symptoms and ultimate receipt of a diagnosis was 15 months; patient and provider delays were equally long, and both appeared to contribute to late-stage disease [21]. Reasons for patient delays cited in studies from sub-Saharan Africa include patients' lack of awareness of breast cancer symptoms and their seriousness [20][21][22][23], fear of a cancer diagnosis [21,23], use of traditional healers [21][22][23], and financial concerns about treatment [20,21]. Provider delays have been less extensively investigated in LMICs, including in sub-Saharan Africa, but lack of breast cancer experience and knowledge among primary care clinicians and limited access to tertiary centers are some of the probable contributors.…”
Section: Breast Cancer Mortality In Lmicsmentioning
confidence: 99%
See 1 more Smart Citation
“…41 In contrast, a study that reported factors associated with patient delay found that self-examination was not associated with this delay (OR=0.73 95% CI 0.31-1.74). 42 However, these studies did not associate self-examination with survival.…”
mentioning
confidence: 92%
“…Reasons adduced for that include poor knowledge of breast cancer risk factors, signs and symptoms [22,23]; lack of awareness coupled with poor attitude to preventive practice [24][25][26][27][28] and late presentation at an advanced stage of the disease [29,30]. Lack of effective national screening programmes against a backdrop of poor socioeconomic status also contribute to the breast cancer burden in resource constrained settings.…”
Section: Discussionmentioning
confidence: 99%